Curcuma longa Hepatotoxicity: A Baseless Accusation. Cases Assessed for Causality Using RUCAM Method - Stati, Gianmarco; Rossi, Francesco; Sancilio, Silvia; Basile, Mariangela; Di Pietro, Roberta (Frontiers in Pharmacology, 2021)
Curcuma longa is a perennial herb that belongs to the Zingiberaceae family. To date, literature includes more than 11.000 scientific articles describing all its beneficial properties. In the last three decades various surveys by the U.S. Food and Drug Administration (FDA) concluded that curcumin, the most active ingredient of the drug, is a “generally safe” compound with strong anti-oxidant effects. Nonetheless, recently several reports on the safety of plant products, pointed out cases of hepatotoxicity linked to consumption of food supplements containing powdered extract and preparations of Curcuma Longa. The latest trend is the use of Curcuma Longa as a weight-loss product in combination with piperine, which is used to increase its very low systemic bioavailability. Indeed, only 20 mg piperine, one of the alkaloids found in black pepper (Piper nigrum), assumed at the same time with 2 g curcumin increased 20-fold serum curcumin bioavailability. This combination of natural products is now present in several weight loss supplements containing Curcuma Longa. The enhanced drug bioavailability caused by piperine is due to its potent inhibition of drug metabolism, being able to inhibit human P-glycoprotein and CYP3A4, while it interferes with UDP-glucose dehydrogenase and glucuronidation activities in liver. While only few cases of hepatotoxicity, assessed using RUCAM method, from prolonged intake of piperine and curcumin have been reported, it would be reasonable to speculate that the suspected toxicity of Curcuma Longa could be due to the concomitant presence of piperine itself. Hence, human trials will be necessary to settle this dispute.